Synthesis of Hydrophobic Silica Xerogel from Fly Ash for Oil–in–Water Adsorption - Ummi Hanifah; Anis Shofiyani; Gusrizal Gusrizal (Jurnal Kimia Sains dan Aplikasi, 2025)
In this study, silica xerogel was synthesized from coal fly ash modified with trimethylchlorosilane (TMCS) reagent to increase the hydrophobicity of the material. TMCS-modified silica xerogel was then used for oil adsorption in water. Silica xerogel was synthesized using the sol-gel method with sodium silicate from fly ash as a precursor and citric acid as a catalyst. The sol-gel process involves sequential steps of hydrolysis and condensation, followed by gelation (the sol-to-gel transition) and aging. Surface modification of the resulting silica xerogel was conducted using TMCS in a mixture of methanol and petroleum benzine, with volume ratios of TMCS:methanol:petroleum benzine set at 0:1:1, 1:1:1, 2:1:1, and 3:1:1. The synthesized silica xerogel was characterized using FTIR spectroscopy, SEM, GSA, and contact angle measurements to evaluate its hydrophobicity. FTIR spectrophotometry results revealed that silica modified with TMCS exhibited absorption bands corresponding to Si–CH3 groups at 843.20, 845.69, and 843.18 cm-1. These findings indicate the successful formation of silyl groups on the surface of the silica xerogel when using TMCS:methanol:phosphate buffer (PB) ratios of 0:1:1, 1:1:1, 2:1:1, and 3:1:1. SEM analysis revealed that the surface morphology of the synthesized silica xerogel exhibited a porous structure with a mesoporous pore size distribution. Based on the experimental results, it can be concluded that surface modification with TMCS enhances the hydrophobicity of the silica xerogel. An increase in TMCS volume led to a corresponding increase in hydrophobicity. The hydrophobic silica xerogel demonstrated a good adsorption capacity for oil in water, ranging from 6 to 22 mg/g, with the adsorption capacity increasing in accordance with the degree of hydrophobicity.